Pengaruh Variasi Temperatur Sumber Panas Terhadap Temperatur Udara Dalam Heater Mesin Stirling - Muhammad Dendy Agusdiandy; Siregar, Zufri Hasrudy; Jufrizal; Hasanah, Moraida (CV. IRA PUBLISHING, 2022)
This research is focused on testing the heat transfer rate from the heat source to the Stirling engine heater. The test was carried out on the Stirling engine heater as a cylindrical tube. This study aims to determine the effect of variations in the heat source's temperature on the heater's air temperature. This test was carried out on a Stirling engine with a gamma-type mechanical configuration. The heat source temperature varied in 3 categories, namely between 860-900℃ (I), 780-850℃ (II), and 710-779℃ (III). there were 3 temperature positions measured, namely the temperature of the heat source, the temperature of the outer wall of the heater, and the temperature of the air in the heater. The fuel used for the heat source is liquefied petroleum gas (LPG). The research results for the heat source temperature in categories I, II, and III resulted in the average temperature on the outside heater wall being 729.8°C, 659.6°C, and 591.3°C, respectively. While the average air temperature in the heater for categories I, II, and III, respectively, is 201.7°C, 130.1°C, and 114.8°C. The 3 variations of heat source temperature show that the given heat source temperature value is very influential and directly proportional to the temperature inside the heater.